Synthesis, Characterization and Microbial Activities of Metal Complexes with 2-[N-(2- Hydroxyphenyl)methylidinyl]amino-4,5-dihydronaphtho[1,2d]thiazole Derivatives - Durg, Vijaykumar; Patil, Nirdosh; Shivaprasad, K.H. (Asian Journal of Chemistry, 2012)
Condensation of substituted salicylaldehydes with primary amine of naphtha-thiazole gave a series of Schiff bases, such as 2-[N-(2-hydroxyphenyl)methylidinyl]amino-4,5-dihydronaphtho- [1,2d]thiazole (HL1); 2-[N-(2-hydroxy 4-methoxyphenyl)methylidinyl]amino-4,5-dihydronaphtho[ 1,2d]thiazole (HL2) and 2-[N-(3,4-dimethoxy-2-hydroxyphenyl)methylidinyl]-amino-4,5-dihyd-ronaphtho[1,2d]thiazole (HL3). All the metal complexes were synthesized by reaction between cobalt(II) chloride, nickel(II) chloride and copper(II) chloride with the ligands (HL1), (HL2) and (HL3). These Co(II), Ni(II) and Cu(II) complexes were characterized by elemental analyses, conductance measurements, magnetic susceptibility measurements, IR, 1H NMR and electronic spectral studies. On the basis of magnetic and spectral studies, octahedral geometry was assigned for these complexes. These complexes have been screened in vitro for their possible antimicrobial activity.